Combined treatment with vemurafenib and cobimetinib in Langerhans cell histiocytosis and Erdheim-Chester disease overlap syndrome: A case Report - Hidalgo-Soto Marta; Poza-Santaella María; Pita-Suárez Daniel; Calbacho-Robles María; Pina-Sánchez José; González-Medina José; Baumann Tycho Stephan (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2022)
Histiocytoses are clonal disorders diseases derived from the monocyte-macrophage lineage. The Erdheim-Chester Disease (ECD) and Langerhans Cell Histiocytosis (LCH) may occur in association with overlapping clinical, histopathological and molecular features, harboring somatic MAP2K1 mutations in more than 50% of patients. BRAF and MEK inhibitors have shown to be efficacious in ECD and LCH, including responses in patients with CNS involvement. This case report describes a 59-year-old woman who presented with vemurafenib-refractory ECD/LCH overlap syndrome treated with vemurafenib/cobimetinib dual therapy, with rapidly progressing neurological involvement after its initiation. Although targeted therapy plays a crucial role in the treatment of histiocytosis, only anecdotal clinical cases treated with dual therapy have been reported in ECD or LCH and collaborative trials are needed to improve outcomes.